Vocabulary of the Streets in a Writer’s Notebook - Gomes de Medeiros, Vanise (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
The main objective of this work, which is part of research of the History of Linguistic Ideas in conjunction with Discourse Analysis, is to investigate the functioning of the glossary of the Brazilian writer João Antônio.